A Study to Assess the Effectiveness of Structured Teaching Programme on Knowledge Regarding Recent Trends in Infertility Management among Staff Nurses Working in SC Hospital, Hassan, Karnataka (International Journal of Nursing Education, 2019)
Background: This study was designed to investigate the knowledge regarding recent trends in infertility management. The validity and reliability of research instruments was established and data was collected from 60 staff nurses selected from sc hospital, hassan, Karnataka using the purposive sampling method. This formed the basis of the detailed analysis and conclusions and recommendations. Aims and objectives: The aim of this study is to find out the the knowledge regarding recent trends in infertility management. Material and method: Pre-experimental research design was adopted to achieve the goal of the study. The tool consists of one parts First part consists socio demographic data consists of Self structured questionare. 60 samples were collected from selected from sc hospital, hassan, Karnataka Result: This study was undertaken to assess the effectiveness of teaching programme, regarding recent trends in infertility management.. The study involves one group pre- test post-test pre experimental design with purposive sampling technique, 60 samples of staff nurses was selected on the basis of inclusion and exclusion criteria. A conceptual framework used for this study was modified “king?s goal attainment model.” Analysis of obtained data was planned based on the objectives and hypothesis of the study, both descriptive and inferential statistics were used for the analysis of the data. The data was interpreted in the forms of tables and graphs. There was a significant increase of 39.3% of knowledge gain after the administration of STP. Staff nurses improved their mean knowledge from 13.76 to 25.57. The difference between pre and posttest knowledge score was highly significant. The paired‘t’ value was 30.51 and that was highly significant at p = 0.001 level. Conclusion: The following conclusion can be drawn from the study findings, which are supported by evidence from the other literature;the self-administered questionare has shown remarkable difference between pre-test and post-test. & STP was effective among staff nurses
Keywords: Structured teaching programme, recent trends, infertility management, Knowledge of staff nurses.